Thermodynamic characterization of solidification and defects that occur in Mg-alloy AM60 (Journal of Mining and Metallurgy, Section B: Metallurgy, 2017)
The AM60 alloy was thermodynamically examined using chemical analysis, thermodynamic calculation made by ThermoCalc program, “in situ” thermal analysis and differential scanning calorimetry (DSC), whereas the microstructure constituents were confirmed using optical and scanning electron microscopy (SEM). The equilibrium solubility of Al in Mg at the eutectic temperature 437 °C is 12.6 wt. % Al. According to the solvus line of the Mg-Al phase diagram the intermetallic compound of Al12Mg17 is precipitating on the boundaries of the primary Mg grains after the completed solidification. Solidification of the AM60 alloy has been investigated using “in situ” simple thermal analysis. The investigation of solidification has been taking place by evaluation of the cooling curves in connection with metallographic examinations, differential scanning calorimetry and thermodynamic calculations. All defects, nonmetallic inclusions and intermetallic compounds that occur in investigated AM60 alloy were identified.